IMPROVING STUDENTS’ VOCABULARY MASTERY USING PLICKERS FOR ELECTRICAL AVIONIC DEPARTMENT - Maria Asumpta Deny Kusumaningrum; Dewanti Ratna Pertiwi (Jurnal Inovasi Penelitian, 2020)
The lack of English vocabulary mastery becomes a problem faced by Electrical Avionic department students at STT Adisutjipto Yogyakarta. Mostly, the students learn about the technical term of vocabulary in their field. Students feel bored to have old dated activities in learning English. They stay in a dormitory without laptop, mobile phone, television, and internet access. They have a pressure to pass the requirement subjects as well as English in accordance with their cooperation with Garuda Indonesia. Based on this problem, the researcher chose online learning media using “Plickers”. Plickers is an online tool that has supporting application for facilitating students without any electronic devices. Because of the urgency for English needs in STT Adisutjipto, this research was conducted to solve the problems occurred. The research aimed to answer a research question which is how Plickers improves students’ vocabulary mastery. The data collected from 24 college students. The researcher applied action research by conducting two cycles through journal log, observation, questionnaire and interview. The students’ vocabulary mastery improvement was measured by comparing the score from mid-term test, students’ project in visiting the workshop and written test. The results of this study showed that there were students’ vocabulary mastery improvements. The online